Examining the Causal Connections Between Multisensory Marketing, Brand Experience, Consumer Perceived Value, and Brand Strength is Part of the Power of Experiential Marketing - Sudarnice; Zainul Wasik; Muchammad Saifuddin (PT. Mawadaku Sukses Solusindo, 2025)
One of the main issues facing brand managers today is giving consumers memorable and unique experiences to establish a solid rapport between the company and its customers. As a result, strategies for experiential marketing that engage all senses have grown in popularity. Nevertheless, the creation of multimodal brand experiences that provide customers a high perceived value and produce strong, long-lasting brand strength is not well understood. We carried out an empirical study in the distinctive service industry of luxury hotels, which offers a good example for learning about an approach that appeals to all senses, in order to better understand the causal relationships between multisensory marketing, brand experience, customer perceived value, and brand strength. Our study's findings provide credence to the idea that creating brand experiences through multimodal marketing is crucial. Both significantly influence brand strength and are crucial factors in determining how much a client thinks a brand is worth. Furthermore, by revealing the causal structure, brand strength may be developed by understanding which aspects of customer perceived value—financial, functional, social, and personal—are most impacted by brand experience and multimodal marketing. Consequently, the findings provide fascinating guidance for developing successful experience marketing.